Content and Competence A Descriptive Approach to the Concept of Rights - Weissinger, Jakob (Mohr Siebeck, 2019)
Just what is a right? Jakob Weissinger approaches this central problem of jurisprudence by critically examining the purpose of such normative concepts and carefully analysing the fundamental elements of normative practice like actions, decisions, the logic of norms and values as well as the plurality of normative practice. Interlinking the insights won, he outlines a stand-alone theory of rights which emphasises the empowering dimension of rights in the process of justifying (legal) rules. Not only does he question well-established theories, such as Hohfeld's famous analysis of legal conceptions, but aspires to set future debates in legal theory, especially those surrounding rights such as the long-standing dispute between interest and choice theories of rights, on new and more solid meta-theoretical ground.